Treating social anxiety disorder remotely with cognitive therapy. (2020) - Warnock-Parkes, Emma; Wild, Jennifer; Thew, Graham R.; Kerr, Alice; Grey, Nick; Stott, Richard; Ehlers, Anke; Clark, David M.
Abstract: Remote delivery of evidence-based psychological therapies via video conference has become particularly relevant following the COVID-19 pandemic, and is likely to be an on-going method of treatment delivery post-COVID. Remotely delivered therapy could be of particular benefit for people with social anxiety disorder (SAD), who tend to avoid or delay seeking face-to-face therapy, often due to anxiety about travelling to appointments and meeting mental health professionals in person. Individual cognitive therapy for SAD (CT-SAD), based on the Clark and Wells (1995) model, is a highly effective treatment that is recommended as a first-line intervention in NICE guidance (NICE, 2013). All of the key features of face-to-face CT-SAD (including video feedback, attention training, behavioural experiments and memory-focused techniques) can be adapted for remote delivery. In this paper, we provide guidance for clinicians on how to deliver CT-SAD remotely, and suggest novel ways for therapists and patients to overcome the challenges of carrying out a range of behavioural experiments during remote treatment delivery. Key learning aims: (1) To learn how to deliver all of the core interventions of CT-SAD remotely. (2) To learn novel ways of carrying out behavioural experiments remotely when some in-person social situations might not be possible.